(untitled) (The Research of Medical Science Review, 2025)
The current study compared the effects of sodium-glucose cotransporter-2 (SGLT2) inhibitors on estimated glomerular filtration rate (eGFR) and urine albuminto-creatinine ratio (ACR) in patients with diabetic chronic kidney disease (CKD) versus those not receiving SGLT-2 inhibitors. Study Design: Cohort Study Study Place: CMH Rawalpindi Materials and Methods: Patients with type 2 diabetes mellitus and chronic kidney disease (stages 2-4, eGFR ≥ 30 mL/min/1.73 m²) were divided into two groups: those treated with SGLT-2 inhibitors (mainly dapagliflozin) and those not treated with these agents. Data was collected retrospectively from hospital records, encompassing ACR and eGFR at baseline and after 24 weeks of followup. Independent t-tests and chi-square tests were utilized for statistical analyses, with significance established at p < 0.05. Results A total of 162 patients were included in the study, with 54 receiving SGLT-2 inhibitors and 108 not receiving them. At baseline, both groups exhibited similar eGFR and ACR levels. Following 24 weeks, patients receiving SGLT-2 inhibitors demonstrated a more significant decrease in eGFR, declining from 67.5 to 65.2 mL/min/1.73 m², in contrast to the non-SGLT-2 group, which decreased from 68.9 to 68.2 mL/min/1.73 m². The reduction in ACR was more significant in the SGLT-2 inhibitor group than the non-SGLT-2 group. Conclusion SGLT-2 inhibitors significantly slowed ACR progression in diabetic CKD patients compared to other glucose-lowering therapies, suggesting their potential as nephroprotective agents in managing CKD.